The position of religious marriage guardians (wali muhakkam) in Islamic law and Indonesian positive law: Analysis of decision number 935/pdt.p/2024/pa.gm - Ayang Afira Anugerahayu; Muhammad Rifaldi Setiawan (Priviet Social Sciences Journal, 2026)
The existence of a marriage guardian (wali nikah) constitutes an essential pillar of marriage that must be fulfilled for a prospective bride under Islamic law and Indonesian positive law. However, in practice, there are marriages conducted without a lineage guardian (wali nasab) or a judicial guardian (wali hakim), instead utilizing a guardian from among religious figures or Islamic scholars (ustadz), commonly referred to as wali muhakkam. This practice is not regulated by the Compilation of Islamic Law (Kompilasi Hukum Islam), resulting in legal uncertainty. This article analyzes the legal standing of religious figure guardians and their sharīʿah and juridical foundations through a case study of the Decision of the Giri Menang Religious Court Number 935/Pdt. P/2024/PA.GM, which validated a marriage officiated by an ustadz acting as wali muhakkam. This study employs a normative legal research method using statutory, conceptual, and case approaches. The findings indicate that, from a fiqh perspective, the appointment of a wali muhakkam may be justified under emergency conditions, whereas under positive law, its existence only attains legal legitimacy through the mechanism of marriage legalization (nikah isbat). The analyzed decision demonstrates a degree of legal adaptability in accommodating social realities based on the principle of maslahah. Therefore, reconstructing the regulation concerning marriage guardians in national law is necessary to ensure that the practice of wali muhakkam no longer remains within a legal gray area.